"A weird culture of coercion": The impact of health care corporatization on clinicians. (24th August 2022) - Rudden, Marie G.
Abstract: This paper describes the nature of today's corporatized health care system in the United States, offering examples of the psychological toll it takes on clinicians at all levels. It details corporate practices that disenfranchise practitioners from exercising their clinical judgment and from offering input to system administrators about problematic patient care experiences. It discusses the sense of frustration, resignation and moral injury that can permeate their work lives and disrupt their sense of effectiveness and well‐being in this context. Following this background is a psychoanalytic analysis of narratives from two physicians about their corporate health care experiences. Two case studies follow, in which a nurse and a physician entered psychoanalytic psychotherapy to process the destructive psychological impact of their work environments. A third case illustrates the negative impact of automatized insurance practices on one psychologist and her patient.